Utilization Of Agricultural Waste-Based Alternative Feed To Improve Productivity And Efficiency Of Sheep - Sri Mahareni Br Sitepu; Media Agus Kurniawan; Griya Eri Enanda (Cattleya Darmaya Fortuna, 2026)
Feed availability and cost remain major constraints in sheep production, particularly in smallholder systems. This study aimed to evaluate the effect of substituting forage with agricultural waste–based concentrate on growth performance and economic efficiency of sheep. A Completely Randomized Design (CRD) was applied using four treatments with six replications (24 sheep) over a 62-day period. The treatments consisted of P0 (100% forage), P1 (70% forage + 30% concentrate), P2 (60% forage + 40% concentrate), and P3 (50% forage + 50% concentrate). Observed parameters included feed intake, average daily gain (ADG), feed conversion ratio (FCR), and cost per kg body weight gain. Data were analyzed using analysis of variance (ANOVA) followed by Duncan’s Multiple Range Test at a 5% significance level. The results showed that increasing the proportion of concentrate significantly (P < 0.05) improved both biological performance and economic efficiency. Feed intake increased from 860.00 to 1021.50 g/head/day, while ADG increased from 87.50 to 142.50 g/head/day. In contrast, FCR decreased from 9.83 to 7.15, indicating improved feed efficiency. Moreover, cost per kg body weight gain decreased substantially from Rp 52,000 to Rp 30,315. Duncan’s test revealed that treatment P3 consistently produced the best results, while P2 showed comparable efficiency in FCR. In conclusion, substituting forage with up to 50% agricultural waste–based concentrate effectively enhances growth performance and reduces production costs in sheep. This feeding strategy is recommended to improve productivity and profitability in small- to medium-scale sheep farming systems.